Diagnosis of nasopharyngeal carcinoma by DNA amplification of epstein-bar virus genomes in tissue obtained by biopsy and fine-needle aspiration - Hassan, Shahid; Yap, Yap; Ravichandran, M.; Chan, Melissa Li-Ann (Pusat Pengajian Sains Perubatan, Universiti Sains Malaysia, 2006)
Background Penemuan Projek/Abstrak (Perfu disediakan makluman di antara 100 - 200 perkataan di dalam Bahasa Malaysia dan Bahasa lnggeris. lni kemudiannya akan dimuatkan ke dalam Laporan Tahunan Sahagian Penyefidikan & Pembangunan sebagai satu cara untuk menyampaikan dapatan projek tuanfpu~n kepada pihak Universiti). (English version) Nasopharyngeal carcinoma (NPC) is common in Malaysia but diagnosis is sometimes delayed for non-representative biopsy, submucosal disease and occult primaries- increasing m·arbidity and mortality. Epstein-Barr virus (EBV) is associated with all types of NPC and DNA in tumor cells is detectable by polymerase chain reaction (PCR). EBV products EBNA 1, EBNA2 and LMP1 are implicated in oncogenesis and is detectable in nodal tissue. However no similar study has been done in Southeast-Asia with adequate sample. Objectives This study evaluates the validity and reliability of detecting EBV genes in biopsy and FNAC tissue in NPC by PCR. Methodology Tissue from 72 nasopharyngeal biopsies were collected from consented patients. 36 were positive and 36 negatives served as controls. Tissue from 70 fine-needle aspirations were similarly obtained. 35 belonged to NPC-positive patients, and 35 of other pathologies served as controls. DNA was extracted, amplified with forward and reverse primers for EBNA 1, EBNA2, LMP1 genes and human a-actin gene as control, and detected by electrophoresis. Cloned DNA from 895-8 cell line served as positive control. Histopathological-proven primary tumour and clinico-pathological criteria for neck nodes (clinically suspicious neck node with histopathologically-confirmed primary tumour) were used as gold standard. Results 35/36 positive nasopharyngeal biopsies and 35/36 negatives contained sufficient DNA. EBNA 1 gene was detected in 34/35 positive specimens but were undetected in the controls. EBNA2 gene was detected in 31/35 positive specimens and in 2/35 controls. LMP1 was detected in 32/35 positive specimens and in 4/35 controls. (P > 0.05 by McNemar_s test-- i.e. no significant difference from histopathology.) EBNA1 has the best sensitivity (97.1%) and specificity (100%) (Kappa = 0.97). One patient in the control group was positive for EBV DNA and developed NPC 1 year later. Another patient with obvious nasopharyngeal tumour was negative on the 1st biopsy and confirmed on repeat biopsy 2 weeks later, but EBV DNA was detected in ~oth specimens. 35/36 metastatic NPC specimens contained sufficient DNA and one was excluded due to presence of second primary. EBNA 1 gene was detected in 30/34 nodes and 1/34 rontro1s. EBNA2 gene was detected in 29/34 nodes and none of the controls. LMP1 gene was detected in 30/34 nodes and in 2134 of controls. (P > 0.05 by McNemar_s test_ i.e. no significant difference from clinico-pathological criteria for neck metastasis). A cut-off point of >0/3 genes offers the highest sensitivity (97.1%} and specificity (94.1%) (Kappa= 0.91 ). All histological types of NPC contained EBV DNA. Conclusion EBV DNA detection is reliable and a~rate in di~gnosing NPC. On par with histopathology in detecting primary tumours, it ~lso predtcts.the dev~l?pment ?f NPC. On par with clinicopathological criteria in detecting metastatic NPC, 1t IS supenor to fine-needle cytology and can suggest NPC in occult primaries